2016
DOI: 10.3390/rs8070560
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dynamics of Inundation Patterns of Two Largest River-Connected Lakes in China: A Comparative Study

Abstract: Poyang Lake and Dongting Lake are the two largest freshwater lakes in China. The lakes are located approximately 300 km apart on the middle reaches of the Yangtze River and are differently connected through their respective tributary systems, which will lead to different river-lake water exchanges and discharges. Thus, differences in their morphological and hydrological conditions should induce individual lake spatio-temporal inundation patterns. Quantitative comparative analyses of the dynamic inundation patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Precipitation is among the important factors that drive the dynamics of surface water areas for southwest Poyang Lake, and these conclusions are consistent with previous studies [ 10 , 56 ]. However, Figure 3 illustrates that the correlation between the surface water area and the accumulated precipitation is very low in some periods.…”
Section: Discussionsupporting
confidence: 93%
“…Precipitation is among the important factors that drive the dynamics of surface water areas for southwest Poyang Lake, and these conclusions are consistent with previous studies [ 10 , 56 ]. However, Figure 3 illustrates that the correlation between the surface water area and the accumulated precipitation is very low in some periods.…”
Section: Discussionsupporting
confidence: 93%
“…Feng et al () used a time series of MODIS data to assess the surface water area of Poyang Lake from 2000 to 2010 and found that the lake area had been extremely variable over this period (Figure ). Feng et al () and Wu and Liu () both compared the pattern of inundation dynamics in Poyang Lake and Dongting Lake using time series MODIS data. Han et al () monitored the wetland change of Poyang Lake over the last four decades using Landsat data series.…”
Section: Spatio‐temporal Monitoringmentioning
confidence: 99%
“…The rates of decrease were small in spring and winter at −4.05 km 2 /a and −0.88 km 2 /a, respectively. These characteristics are related to precipitation, temperature conditions, the operation of the Three Gorges Reservoir (TGR), and the main flood season of the Yangtze River in the Dongting Lake region [73,91]. The seasonal and interannual changes in the water area of Dongting Lake from 2001 to 2017 are shown in Figure 5.…”
Section: Analysis Of the Interannual And Seasonal Changes In The Watementioning
confidence: 99%
“…This lake represents an important regional fishery and tourism resource; correspondingly, the existence and stability of the lake play irreplaceable roles in the development of the regional economy and the balance of the regional environment. However, due to intensified human activities and climate change, the occurrence of algal blooms and the reduction in the water surface area have considerably impacted Dongting Lake and its surrounding environment [72][73][74][75][76]. Additionally, these factors have limited the supply of freshwater to the surrounding population [77,78].…”
Section: Introductionmentioning
confidence: 99%